English Teachers’ Innovative Approach to Teaching Speaking Skills - Nandita Fitriani (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Teachers hardly provide practical and experiential skills involving problem solving that students may use to deal with everyday matters (Anburaj, Christopher, & Ming, 2014). When students fail to acquire practical and problem-solving abilities in school, it can complicate their transition from academic life to real-world challenges. According to Uyun (2022), most Indonesian schools do not teach English writing, reading, speaking, and listening skills that apply to their daily lives. They tend to teach students with mostly grammatical and theoretical knowledge instead. Therefore, teachers need to embrace innovative ways to enhance both the teaching process and the results that students will achieve. Yamin and Purwati (2021) addressed innovative teaching as a way for teachers or schools to improve learning to be more effective and suited to the student’s needs by embracing creative and innovative methods, strategies or materials.
Reupload file repository 30 Maret 2026_Ratna
Keywords: English Teachers’ Innovative Approach; Teaching Speaking Skills